1998
DOI: 10.1128/cmr.11.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Structures ofToxoplasma gondiiTachyzoites, Bradyzoites, and Sporozoites and Biology and Development of Tissue Cysts

Abstract: SUMMARY Infections by the protozoan parasite Toxoplasma gondii are widely prevalent worldwide in animals and humans. This paper reviews the life cycle; the structure of tachyzoites, bradyzoites, oocysts, sporocysts, sporozoites and enteroepithelial stages of T. gondii; and the mode of penetration of T. gondii. The review provides a detailed account of the biology of tissue cysts and bradyzoites including in vivo and in vitro development, methods of separation from host tissue, tissue cyst rup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
706
1
151

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 992 publications
(867 citation statements)
references
References 143 publications
(204 reference statements)
9
706
1
151
Order By: Relevance
“…The observation that nonencysted stages in the skeletal muscles, tongue, and diaphragm exhibit bradyzoite markers is surprising. In vitro studies with T. gondii indicate that the BAG-5 antigen is an early developing bradyzoite marker (Dubey et al 1998b). Therefore, stages expressing the BAG-5 antigen might not be fully mature bradyzoites.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that nonencysted stages in the skeletal muscles, tongue, and diaphragm exhibit bradyzoite markers is surprising. In vitro studies with T. gondii indicate that the BAG-5 antigen is an early developing bradyzoite marker (Dubey et al 1998b). Therefore, stages expressing the BAG-5 antigen might not be fully mature bradyzoites.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning other developmental stages of T. gondii (for review, see Dubey et al 1998), the presence of an OMC complex has not been explicitly determined yet. Nondividing bradyzoites, strain ME49, which were purified from the brains of mice 2 months after infection, failed to reveal such structure (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Both the parasite's proliferating tachyzoite form and the slowly dividing bradyzoite stage were shown to possess a relatively characteristic mitochondrial ultrastructure including a dualmembraned wall with vesicular cristae permeating a substantial matrix space (van der Zypen and Piekarski 1967; Dubey et al 1998). However, serial-sectioned T. gondii tachyzoites recently prepared to analyze the apicoplast (Köhler 2005), a plastid-like organelle of Apicomplexa, strongly suggested that T. gondii tachyzoites might also possess a greater diversity regarding its mitochondrial architecture as presently discussed.…”
Section: Introductionmentioning
confidence: 98%
“…T. gondii has various infectious stages that have a similar ultrastructure but dier in the rhoptries (Dubey et al 1998). Accumulating evidence indicates that a vaccine of stage-speci®c antigen leads stage-limited protection (reviewed by Alexander et al 1996).…”
Section: Discussionmentioning
confidence: 99%